Influence of structural factors on physico-chemical properties of glasses and glass coatings in alkalialumoborosilicate system - Shalygina, O.; Voronov, G.; Tymoshenko (Mironova), G.; Odintsova, A. (Functional Materials, 2016)
It was revealed the degree of impact of structural factors on physical and chemical properties of glasses and glass coatings, particularly chemical resistance, water resistance, surface-tension of and spreading in the R₂O-R´O-Al₂O₃-B₂O₃-SiO₂ system. It was determined clear boundaries of the values of the structural factors and their relationship with the glass chemical composition. The basic principles of synthesis of multifunctional glass matrices - bases of chemically resistant fusible glass coating were developed.